Saxifraga tricuspidata Rottboll - Desjardins, Émilie; Lai, Sandra; Payette, Serge; Dubé, Martin; Sokoloff, Paul C.; St-Louis, Annie; Poulin, Marie-Pier; Legros, Jade; Sirois, Luc; Vézina, François; Tam, Andrew; Berteaux, Dominique (Zenodo, 2021)
Saxifraga tricuspidata Rottbøll Figure 17G Materials examined. CANADA – Nunavut • Ellesmere Island, CFS Alert; 82°26′39″N, 61°57′18″W; 159 m a.s.l.; 26 Jul. 2019; habitat: mesic, with till and rocks as substrates, dominated by Juncus biglumis , moss, and lichen; QFA0635004. Identification. Plants 3.5–7.5 cm high; herbaceous; caespitose (cushion shape). Taproots and rhizomes present. Stems 2.5–7.0 cm long; erect; hairy, with glandular hairs. Leaves basal and cauline; heterophyllous; alternate; subsessile (basal leaves) or sessile (cauline leaves). Basal leaf blades 3–10 mm long, 1.5–4.0 mm wide; linear or oblanceolate; bases cuneate; lobed, with 1–3 triangular, cuspidate lobes; green or red; abaxial and adaxial surfaces both glabrous; margins ciliate, with non-glandular hairs. Cauline leaf blades 2.5–6.5 mm long, 0.5–1.5 mm wide; elliptic or oblanceolate; unlobed or sometimes lobed, with narrow triangular lobes; abaxial and adaxial surfaces both glabrous; margins ciliate, with non-glandular hairs; apices cuspidate. Inflorescence a cyme, with 2–7 flowers. Pedicels hairy. Sepals 5; 1.5–2.0 mm long, 0.8– 1.5 mm wide; ovate; green or purple; surface glabrous; margins glabrous; apices obtuse. Petals 5; 2.5–5.0 mm long, 1–3 mm wide; obovate or oblanceolate; unlobed; ivory or yellow, with apically yellow, orange, or red dots. Androecium with 10 stamens and 0.3–0.7 mm long anthers. Gynoecium with 2 styles. Characteristics allowing to distinguish S. tricuspidata from the other Saxifraga species present on Ellesmere Island can be found under S. cernua . Published as part of Desjardins, Émilie, Lai, Sandra, Payette, Serge, Dubé, Martin, Sokoloff, Paul C., St-Louis, Annie, Poulin, Marie-Pier, Legros, Jade, Sirois, Luc, Vézina, François, Tam, Andrew & Berteaux, Dominique, 2021, Survey of the vascular plants of Alert (Ellesmere Island, Canada), a polar desert at the northern tip of the Americas, pp. 181-225 in Check List 17 (1) on page 219, DOI:10.15560/17.1.181